Tanggung Jawab Pihak Pengelola Aplikasi Jual Beli Online (Shopee) Terhadap Penjualan Produk Tiruan Merek Terkenal - Ansa, Ferdi; Umam, Haerul; Taufik Asrianto, Muhammad (Universitas Ekasakti, 2023)
This study aims to determine the responsibility of the manager of the online buying and selling application (Shopee) for the sale of counterfeit products of well-known brands and legal protection for owners of well-known brands in selling counterfeit products through online buying and selling applications (shopee). The type of research used is normative legal research. The object of study in this research is the Civil Code, Law Number 20 of 2016 concerning Marks and Geographical Indications, Law Number 19 of 2016 concerning Information and Electronic Transactions, law books and legal journals from various media related to this research. The results of this study indicate that the responsibility of the manager of the Shopee buying and selling application is to sell famous brand counterfeit products. In the form of action if there is a report from the owner of IPR or in the sense of the owner of a well-known mark. The legal protection of well-known brand owners is contained in Law Number 20 of 2016 concerning Marks and Geographical Indications where in the event of a trademark violation in the Shopee online buying and selling application, it is repressive protection in the form of being able to file a lawsuit against article 83 paragraph (1) and also article 1365 of the Civil Code. This proves that saving legal loopholes when infringement of well-known marks is an initiative of the brand owner, and the absence of preventive protection in the form of prudence and responsibility to protect well-known brand owners, thereby harming brand owners when their brand products are imitated and traded without rights in buying and selling applications. online shopee.